2009
DOI: 10.1021/om8006322
|View full text |Cite
|
Sign up to set email alerts
|

(Pyrazol-1-ylmethyl)pyridine Nickel Complexes: Ethylene Oligomerization and Unusual Friedel−Crafts Alkylation Catalysts

Abstract: The reactions of 2,6-bis(3,5-dimethylpyrazol-1-ylmethyl)pyridine (L1) and 2,6-bis(3,5-di-tert-butylpyrazol-1-ylmethyl)pyridine (L2) with NiCl 2 or NiBr 2 gave the nickel(II) complexes [NiCl 2 (L1)] (1), [NiBr 2 (L1)] (2), [NiCl 2 (L2)] (3), and [NiBr 2 (L2)] (4) in high yields. Compounds 2-(3,5-dimethylpyrazol-1-ylmethyl)pyridine (L3) and 2-(3,5-di-tert-butylpyrazol-1-ylmethyl)pyridine (L4) on the other hand gave either mononuclear or dinuclear nickel(II) complexes, depending on the steric bulk of the substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 39 publications
(31 reference statements)
10
47
0
1
Order By: Relevance
“…Nickel catalysts are generally known for dimerizing ethylene, and since low amounts of butenes in these reactions resulted in more ethyltoluenes, it is not surprising the nickel catalyst produced mainly butyltoluenes. But compared to other pyrazolyl nickel catalysts reported in the literature 11,12 that convert all ethylene oligomers from ethylene to alkyltoluenes, the current nickel catalysts are not able to convert all the butenes produced to butyltoluenes in spite of the large amount of EtAlCl 2 used in these reactions. This suggests that the Friedel-Crafts alkylation is not catalyzed by the excess EtAlCl 2 alone, otherwise all the ethylene reactions with the nickel complexes 6-10 would have produced exclusively butyltoluenes from butenes present in the product mix.…”
Section: Effects Of Temperature Time and Pressure Variation On Catalmentioning
confidence: 57%
See 2 more Smart Citations
“…Nickel catalysts are generally known for dimerizing ethylene, and since low amounts of butenes in these reactions resulted in more ethyltoluenes, it is not surprising the nickel catalyst produced mainly butyltoluenes. But compared to other pyrazolyl nickel catalysts reported in the literature 11,12 that convert all ethylene oligomers from ethylene to alkyltoluenes, the current nickel catalysts are not able to convert all the butenes produced to butyltoluenes in spite of the large amount of EtAlCl 2 used in these reactions. This suggests that the Friedel-Crafts alkylation is not catalyzed by the excess EtAlCl 2 alone, otherwise all the ethylene reactions with the nickel complexes 6-10 would have produced exclusively butyltoluenes from butenes present in the product mix.…”
Section: Effects Of Temperature Time and Pressure Variation On Catalmentioning
confidence: 57%
“…But in these dimerization and trimerization reactions, the role of alkylaluminium co-catalysts has only recently been brought into focus following reports by Dyer et al, 9 Gao et al, 10 Ojwach et al 11 and Budhai et al 12 These reports on ethylene oligomerization and post-oligomerization Friedel-Crafts alkylation of toluene show the importance of EtAlCl 2 as a co-catalyst and the solvent in which the ethylene oligomerization reactions are run. Dyer et al, 9 Gao et al, 10 Ojwach et al 11 and others 12 have all reported the formation of alkyltoluenes as secondary products. However, only selected nickel catalysts from the Dyer 9 and Gao 10 systems gave Friedel-Crafts alkylation secondary products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En 2009 Darkwa et al, informaron que complejos derivados de ligandos 2,6-bis(pirazolilmetil)piridina y activados con EtAlCl2, son activos en reacciones de oligomerización de etileno (Ojwach et al, 2009). …”
Section: Complejos Pincer De Níquel(ii) Activos En Polimerizacióunclassified
“…[4][5][6][7][8] Another family of active late transition metal polymerization catalysts based on pyrazol and poly(pyrazolyl) ligands has been described. [9][10][11][12][13][14][15][16] These types of ligands are attractive since their steric and electronic properties can be changed by the appropriate selection of the substituents in the pyrazol ring.…”
Section: Introductionmentioning
confidence: 99%